Micturition diary as a behavioral therapy and its importance in the rehabilitation of neurogenic bladder - Santos Tolentino, Gisélia; Gongora Mantellatto, Vivian; Oliva Zanotto, Camila; Pinheiro, Rodrigo Luiz; Pereira Gabriel, Simone; Murayama (O Mundo da Saúde, 2006)
Neurogenic bladder is the term used to refer to a vesical dysfunction caused by an injury of the nervous system whose cause can be congenital or acquired. Its therapeutic consists in different techniques, but all have as the main objective to preserve the renal function and to prevent the appearance of injuries in the perianal region. The aim of this work is to identity the urinary habit of people affected by neurogenic bladder through the micturitional diary, in the attempt to establish the best behavior of re-education of the vesical function. The methodology employed was the revision of specific literature on micturitional dysfunction of neurogenic origin. It is observed that the micturitional diary is a simple and cheap investigative method, having an extreme importance to characterize patients’ micturitional habits patient, allowing the nurse to establish the therapy most adequate to the type of bladder and the necessities of each individual. This way, one can obtain the patient’s adhesion to the treatment, prevent possible complications and promote the development of her autonomy. Assuring quality of life and social reintegration of these people is the role of the health professional and especially of the nurse.